2013
DOI: 10.1590/s0100-83582013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus growth in silvopastoral system under different crown dia meters

Abstract: -The aim of this study was to evaluate the effect of different crown diameters on the early growth of eucalyptus intercropped withKeywords: agroforestry systems, weed competition, control ranges.RESUMO -Objetivou-se neste trabalho avaliar o efeito de diferentes diâmetros de coroamento sobre o crescimento inicial de plantas de eucalipto em sistema silvipastoril com Brachiaria decumbens. O experimento foi realizado em área de pastagem estabelecida de B. decumbens, na qual foi plantado o eucalipto híbrido urogran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The application of herbicides is necessary at various stages of a forest cycle, it consists of controlling invasive plants with the use of herbicides. This practice allows the crop of interest to grow without competition for water, light and nutrients (MACHADO et al, 2014).…”
Section: Application Technologymentioning
confidence: 99%
“…The application of herbicides is necessary at various stages of a forest cycle, it consists of controlling invasive plants with the use of herbicides. This practice allows the crop of interest to grow without competition for water, light and nutrients (MACHADO et al, 2014).…”
Section: Application Technologymentioning
confidence: 99%
“…After testing crown diameters (weed free distance around plants), Machado et al (2013) concluded plants without crowning showed lower growth. Crown diameters about 2 m provided favorable conditions for initial growth of eucalypt seedlings.…”
Section: Negative Effects Of Weeds In Eucalyptmentioning
confidence: 99%
“…The choice of the tree species that will compose the ICLF system is characterized as a fundamental requirement in the adoption of this agricultural production model (Machado et al 2013). The eucalyptus cultivated in integrated production systems can be useful to several uses, however the commercial use as wood for sawmill, is the one that has been most used by producers, due to the greater nancial return (Oliveira et al 2015).…”
Section: Introductionmentioning
confidence: 99%